2021
DOI: 10.1002/cssc.202100846
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Channel Model for Electron Transfer in a Dye‐Catalyst‐Dye Supramolecular Complex for Photocatalytic Water Splitting

Abstract: To improve the performance of dye‐sensitized photoelectrochemical cell (DS‐PEC) devices for splitting water, the tailoring of the photocatalytic four‐photon water oxidation half‐reaction represents a principle challenge of fundamental significance. In this study, a Ru‐based water oxidation catalyst (WOC) covalently bound to two 2,6‐diethoxy‐1,4,5,8‐diimide‐naphthalene (NDI) dye functionalities provides comparable driving forces and channels for electron transfer. Constrained ab initio molecular dynamics simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…Earlier constrained AIMD simulations in our group have shown that electron transfer in 2 is strongly inhibited once the CÀ NÀ CÀ C torsional mode at the WOC-dye interface is fixed. [25,26] The results presented in this paper provide a rationale behind this observation: The energy gap between the two adiabatic states in the region of the transition state is around 0.1 eV, which is indeed comparable to the energy associated with the torsional mode discussed in ref. [26] The resonance between the torsional mode frequency and the electronic energy gap between the reactant and product states, leads to a deterministic conversion pathway from the reactant to the product.…”
Section: Exploring the Excited State Potential Energy Surfaces With T...supporting
confidence: 80%
See 1 more Smart Citation
“…Earlier constrained AIMD simulations in our group have shown that electron transfer in 2 is strongly inhibited once the CÀ NÀ CÀ C torsional mode at the WOC-dye interface is fixed. [25,26] The results presented in this paper provide a rationale behind this observation: The energy gap between the two adiabatic states in the region of the transition state is around 0.1 eV, which is indeed comparable to the energy associated with the torsional mode discussed in ref. [26] The resonance between the torsional mode frequency and the electronic energy gap between the reactant and product states, leads to a deterministic conversion pathway from the reactant to the product.…”
Section: Exploring the Excited State Potential Energy Surfaces With T...supporting
confidence: 80%
“…[25,26] The results presented in this paper provide a rationale behind this observation: The energy gap between the two adiabatic states in the region of the transition state is around 0.1 eV, which is indeed comparable to the energy associated with the torsional mode discussed in ref. [26] The resonance between the torsional mode frequency and the electronic energy gap between the reactant and product states, leads to a deterministic conversion pathway from the reactant to the product. These results show that vibronic coupling is an important mechanistic aspect to It is observed that for the reactant structure, the first excited state is a charge transfer excitation from the ruthenium catalyst to the NDI, while for the product structure, the excitation corresponds to a charge transfer from the NDI to the ruthenium center.…”
Section: Exploring the Excited State Potential Energy Surfaces With T...supporting
confidence: 80%
“…68 The conservation of spin of an intermediate may also affect the selectivity. 69 However, including these two effects is beyond the scope of the current study and will be a subject of future investigations. Furthermore, the IR peak corresponding to the *CO intermediate is not observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another interesting finding to note is that there is a precise matching between the bottom of the CB and *CH 2 O intermediate, which may enhance the reaction rate by vibronic coupling . The conservation of spin of an intermediate may also affect the selectivity . However, including these two effects is beyond the scope of the current study and will be a subject of future investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The former can be evaluated by investigating the seam-of-crossing (SX) region between the initial and final diabatic states. This can be done by optimizing an SX structure or by a confined sampling such as the blue-moon or umbrella sampling on the corresponding reaction coordinate [26][27][28] . Molecular dynamics simulations, such as surface hopping, are useful to account for the latter dynamics effects 9,[29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%